2020
DOI: 10.1109/jeds.2020.2981974
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of a Novel Si Line Tunneling TFET With High Drive Current

Abstract: In this paper, an N-type silicon line tunneling TFET (LT-TFET) with an ultra-shallow N + pocket was proposed. The pocket was formed by using the germanium preamorphization implantation (Ge PAI), arsenic ultra-low energy implantation and spike annealing. Due to the Ge PAI, the tunneling probability was improved significantly. As a result, a high on-state current of 40µA/µm, a minimum subthreshold swing (SS) of 69 mV/decade and an average SS of 80 mV/decade over 5 decades of drain current were achieved with V DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 22 publications
1
9
0
1
Order By: Relevance
“…The authors fabricated a charge plasma diode considering the work-function difference between the metal contact and the intrinsic silicon body. Similarly, Cheng et al proposed the fabrication of a pocket in the source region of TFET, 33 which confirms the fabrication possibility of the suggested device. However, the step-by-step fabrication flow of SP-CPTFET is shown in Fig.…”
Section: Fabrication and Simulation Processsupporting
confidence: 62%
“…The authors fabricated a charge plasma diode considering the work-function difference between the metal contact and the intrinsic silicon body. Similarly, Cheng et al proposed the fabrication of a pocket in the source region of TFET, 33 which confirms the fabrication possibility of the suggested device. However, the step-by-step fabrication flow of SP-CPTFET is shown in Fig.…”
Section: Fabrication and Simulation Processsupporting
confidence: 62%
“…On this basis, [9] details the selection of specific materials in the channel region, such as group III-V semiconductors, InAs or GaSb, and points out their significant impact on the tunneling probability and current. The discussion of the importance of material selection for optimizing TFET performance is further extended in [13], which examines materials such as III-V compound semiconductors, germanium, nanowires, and carbon-based nanomaterials as potential solutions to the low ion limitation challenge of TFETs.…”
Section: Materials Selectionsmentioning
confidence: 99%
“…In classifying isolation and implantation techniques, Cheng et al, offer noteworthy methods for silicon-based TFETs [13]. It employs Local Oxidation of Silicon (LOCOS), P-well, and fluorine and molecular boron difluoride (BF2) implantations along with Ge pre-amorphization implantation (PAI) combined with ultra-low energy implantation.…”
Section: Fabrication Techniquesmentioning
confidence: 99%
“…At such scaled nano‐dimensions, especially for heterojunction designs, studies on the design reliability aspects become essential; 2,6,16,17,22,23 however, not much work has been that in that respect. Further, designs particularly based on SiGe/Si line tunneling heterojunctions 7‐14 that have been actually demonstrated till now adhere to fabricated Si pockets lying in the range of 6‐7 nm, 7,10 with the very recent gate‐normal TFET comprising a relaxed ~10 nm line pocket 9 . Further, circuit level studies have revealed a potential for excellence; 13 however, at the cost of very high overshoots/undershoots 14 …”
Section: Introductionmentioning
confidence: 98%
“…Therefore, counter‐doped line horizontal pockets (HPs) below gates were reported, which reduced the high onset voltage requirements as well as the gate variability effects 3 . Since then, line TFETs based on ultra‐thin pockets have gained popularity 4‐20 …”
Section: Introductionmentioning
confidence: 99%